Solid-liquid double-phase metal catalytic system as well as preparation method and application thereof
Through the solid-liquid biphasic metal catalytic system, the combination of Bi-Sn-Cu alloy and Ni-Mo alloy is used to solve the problems of low catalytic activity and reduced reaction area in the alkane cracking reaction, and an efficient alkane cracking reaction is achieved.
Patent Information
- Application Number
- CN202510005588.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-14
AI Technical Summary
The existing solid and liquid metal catalysts have problems such as low catalytic activity, reduced reaction area and low catalytic efficiency in the alkane cracking reaction.
A solid-liquid biphasic metal catalytic system is adopted, including Bi-Sn-Cu alloy as liquid phase alloy and Ni-Mo alloy as solid phase alloy. The catalytic system is prepared by heating and mixing to ensure that the solid phase alloy is suspended and rolled in the liquid phase alloy, and sufficient reaction contact is achieved.
The alkane cracking rate and catalytic cracking efficiency are improved, the catalytic alkane cracking rate can reach 98.4%, and the average cracking rate can reach 0.28g/h/kg of catalyst.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic reaction, and in particular to a solid-liquid dual-phase metal catalytic system and a preparation method and application thereof. Background Art
[0002] With the development of economy, people are in urgent need of developing new environmentally friendly energy. Hydrogen energy is an efficient and environmentally friendly secondary energy source, which has been valued as early as the last century. Nowadays, hydrogen is often used as fuel for batteries. Compared with traditional battery fuels, fossil fuels, which have low combustion efficiency and produce a lot of pollutants, hydrogen only produces water after combustion, has no pollution emissions, and has high combustion efficiency. Moreover, hydrogen is a renewable raw material with abundant sources. Obtaining hydrogen and high-value carbon through alkane cracking is one of the most promising hydrogen and carbon production processes.
[0003] The completion of alkane cracking requires the participation of a catalyst. Currently, the commonly used catalysts for alkane cracking are solid metal catalysts and liquid metal catalysts. However, both catalysts have certain disadvantages. The solid metal catalyst is generally made into a loose and porous metal ball. The alkane gas flows through the solid metal catalyst metal ball, and a cracking catalytic reaction is invented on the surface of the ball. However, as the reaction proceeds, the surface of the ball is gradually covered with carbon powder, and the effective reaction area is continuously reduced, resulting in rapid deactivation of the solid electrolyte. Inert gas purging and mechanical vibration are required to remove the surface deposited carbon powder, and the carbon powder in the loose gaps cannot be completely removed; after the liquid metal catalyst is completely melted, the alkane gas passes through the entire liquid column, and the bubbles are fully catalytically cracked in the liquid metal catalyst. The carbon powder generated by the reaction will float to the surface of the liquid. Although the problem of inactivation of the solid catalyst is solved, the catalytic efficiency of the liquid metal catalyst itself is low. For example, the prior art provides a liquid catalyst for cracking alkanes, but the product yield of the catalyst catalysis can only reach 89%, which cannot meet the needs of practical applications.
[0004] In summary, the solid catalysts currently used are easily deactivated, resulting in a pause in production rhythm, thus causing the problem of low efficiency, and the liquid catalysts have the problem of low catalytic efficiency; the catalytic performance of commonly used solid catalysts and liquid catalysts still cannot meet the needs of practical applications. Summary of the invention
[0005] The object of the present invention is to provide a solid-liquid biphase metal catalyst system and a preparation method and application thereof. The solid-liquid biphase metal catalyst system provided by the present invention has high catalytic activity, high catalytic alkane cracking rate and high alkane cracking efficiency.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a solid-liquid biphase metal catalytic system, comprising a liquid phase alloy and a solid phase alloy; in terms of weight percentage, the content of the liquid phase alloy is 20-30%, and the content of the solid phase alloy is 70-80%; the liquid phase alloy is a Bi-Sn-Cu alloy, and the solid phase alloy is a Ni-Mo alloy.
[0008] Preferably, the chemical composition of the Bi-Sn-Cu alloy is 30-40% Bi, 20-30% Sn and 35-45% Cu in weight percentage.
[0009] Preferably, the chemical composition of the Ni-Mo alloy is 55-63% Ni and 37-45% Mo in weight percentage.
[0010] Preferably, the particle size of the Ni-Mo alloy is 1 to 3 mm.
[0011] Preferably, the density of the liquid phase alloy in the solid-liquid dual-phase metal catalyst system is 90-95% of the density of the solid phase alloy.
[0012] The present invention also provides a method for preparing the solid-liquid dual-phase metal catalyst system described in the above technical solution, comprising: heating Bi-Sn-Cu alloy and Ni-Mo alloy particles to 900-1000° C. to obtain a solid-liquid dual-phase metal catalyst system.
[0013] Preferably, the method for preparing the Ni-Mo alloy particles comprises the following steps:
[0014] (1) melting the alloy raw materials and refining them to obtain a Ni-Mo alloy melt;
[0015] (2) pouring and cooling the Ni-Mo alloy melt obtained in step (1) to obtain an alloy ingot; the cooling rate is 150 to 200° C. / min;
[0016] (3) Crushing the alloy ingot obtained in step (2) to obtain Ni-Mo alloy particles.
[0017] Preferably, in step (2), low temperature gas is used for cooling; the temperature of the low temperature gas is -196 to -190°C, the inlet pressure is ≥0.5MPa, and the flow rate is ≥30m 3 / min; the cooling time is ≥10min.
[0018] The present invention also provides the use of the solid-liquid biphasic metal catalyst system described in the above technical solution or the solid-liquid biphasic metal catalyst system prepared by the above preparation method in catalyzing alkane cracking reactions.
[0019] Preferably, the reaction temperature of the alkane cracking is 900-1000°C.
[0020] The present invention provides a solid-liquid biphase metal catalyst system, the chemical composition of which is 20-30% Bi-Sn-Cu alloy and 70-80% Ni-Mo alloy by weight percentage. The present invention uses Bi-Sn-Cu alloy as the liquid phase alloy, Bi and Sn can effectively carry the solid phase catalyst, ensuring the suspension of the solid phase catalyst in the liquid phase catalyst; Sn can also adjust the density of the liquid phase catalyst to ensure that the density of the liquid phase catalyst and the solid phase catalyst are similar, further ensuring the suspension of the solid phase catalyst; Cu is used as an activator to effectively enhance the catalytic activity of the liquid phase catalyst, further improving the alkane cracking rate and catalytic cracking efficiency; Ni-Mo alloy is used as the solid phase alloy to ensure that the density of the solid phase alloy catalyst is similar to that of the liquid phase alloy catalyst, and the tumbling of the solid phase catalyst in the liquid phase catalyst is achieved. Suspension ensures that the catalyst has sufficient reaction contact area while effectively separating the carbon powder, thereby improving the catalytic activity; when the dual-phase metal catalyst system is used to catalyze the cracking of alkanes, under the action of low-blowing alkanes, the Ni-Mo solid phase alloy continues to roll and dynamically suspend in the Bi-Sn-Cu liquid phase alloy, thereby achieving sufficient contact reaction between the catalyst system and the alkanes, and the Ni-Mo solid phase alloy rolls and is flushed by the alkanes, and the carbon powder produced by cracking can quickly separate from the surface of the Ni-Mo solid phase catalyst, thereby effectively ensuring the catalytic activity of the solid phase catalyst, and improving the cracking rate of alkanes and the catalytic cracking efficiency. The results of the examples show that the alkane cracking rate of the solid-liquid dual-phase metal catalyst system provided by the present invention can reach 98.4%, and the average cracking rate can reach 0.28g / h / kg catalyst. DETAILED DESCRIPTION
[0021] The invention provides a solid-liquid biphase metal catalytic system, comprising a liquid phase alloy and a solid phase alloy; in terms of weight percentage, the content of the liquid phase alloy is 20-30%, and the content of the solid phase alloy is 70-80%; the liquid phase alloy is a Bi-Sn-Cu alloy, and the solid phase alloy is a Ni-Mo alloy.
[0022] The solid-liquid biphase metal catalytic system provided by the present invention includes a liquid phase alloy, and the liquid phase alloy is a Bi-Sn-Cu alloy. In the present invention, the liquid phase alloy Bi-Sn-Cu alloy has the advantages of low melting point, high fluidity, low boiling point, and high vapor pressure. The low melting point and high fluidity enable the liquid phase alloy to be used as a good solvent to achieve suspension of the solid phase alloy.
[0023] As an embodiment of the present invention, the Bi-Sn-Cu alloy may include Bi 30-40% by weight, and the Bi may also be 34-36%; in an embodiment of the present invention, the Bi may specifically be 30%, 32%, 34%, 35%, 36%, 37% or 40%. In the present invention, Bi as the main liquid phase solvent can effectively carry the solid phase catalyst and ensure the suspension of the solid phase catalyst in the liquid phase catalyst.
[0024] As an embodiment of the present invention, the Bi-Sn-Cu alloy may include Sn 20-30% by weight, and the Sn may also be 24-26%; in an embodiment of the present invention, the Sn may be specifically 20%, 22%, 24%, 25%, 26%, 27% or 30%. In the present invention, Sn can effectively carry the solid phase catalyst to ensure the suspension of the solid phase catalyst in the liquid phase catalyst; at the same time, the density and melting point of the liquid phase catalyst are adjusted to ensure that the density of the liquid phase catalyst and the solid phase catalyst are similar, further ensuring the suspension of the solid phase catalyst.
[0025] As an embodiment of the present invention, the Bi-Sn-Cu alloy may include 35-45% Cu, and the Cu may also be 38-42% by weight; in an embodiment of the present invention, the Cu may be specifically 35%, 36%, 38%, 40%, 42%, 43% or 45%. In the present invention, Cu is used as an activator to effectively enhance the catalytic activity of the liquid phase catalyst, further improving the alkane cracking rate and catalytic cracking efficiency.
[0026] In terms of weight percentage, the content of the liquid phase alloy is 20-30%, preferably 22-27%, and more preferably 24-26%.
[0027] The solid-liquid dual-phase metal catalyst provided by the present invention also includes a solid-phase alloy, and the solid-phase alloy is a Ni-Mo alloy. In the present invention, the solid-phase alloy has excellent catalytic activity and low vapor pressure, and at the same time has excellent resistance to molten salt corrosion, which is conducive to the long-term stability of the solid-phase alloy in the liquid-phase alloy, and the adjustable density range is large, which is conducive to the suspension and tumbling of the solid-phase alloy in the liquid-phase alloy.
[0028] As an embodiment of the present invention, the Ni-Mo alloy may include 55-63% Ni, and the Ni may also be 58-62% by weight; in an embodiment of the present invention, the Ni may be specifically 30%, 55%, 56%, 58%, 60%, 62% or 63%. In the present invention, a proper amount of Ni can regulate the density of the solid phase alloy to ensure that the solid phase alloy can be suspended in the liquid phase alloy; at the same time, it provides catalytic activity, further improving the alkane cracking rate and catalytic cracking efficiency.
[0029] As an embodiment of the present invention, the Ni-Mo alloy may include 37-45% Mo, and the Mo may also be 38-42% by weight; in an embodiment of the present invention, the Mo may specifically be 30%, 37%, 38%, 40%, 42%, 43% or 45%. In the present invention, an appropriate amount of Mo can effectively improve the catalytic activity of the catalytic system, and further improve the alkane cracking rate and catalytic cracking efficiency.
[0030] As an embodiment of the present invention, the particle size of the Ni-Mo alloy can be 1 to 3 mm, or 2 to 2.5 mm. In the present invention, by controlling the particle size of the Ni-Mo alloy, the solid phase alloy catalyst has a high specific surface area, and ensures that the solid phase catalyst can be suspended and tumbled in the liquid phase catalyst, so that the catalyst is fully in contact with the alkane gas, further improving the catalytic activity of the catalyst; at the same time, it is avoided that the size is too small to be effectively separated from the cracking product carbon powder.
[0031] In terms of weight percentage, the content of the solid phase alloy is 70-80%, preferably 73-78%, and more preferably 74-76%.
[0032] As an embodiment of the present invention, the density of the liquid phase alloy in the solid-liquid dual-phase metal catalyst system can be 90-95% of the density of the solid phase alloy, or 92-93%. In the present invention, by limiting the relationship between the density of the Bi-Sn-Cu alloy and the solid density of the Ni-Mo alloy, the effective suspension of the solid phase alloy in the liquid phase alloy is ensured, the solid phase alloy is prevented from sinking to the bottom or floating, and sufficient reaction contact area is obtained, thereby further improving the alkane cracking rate and catalytic cracking efficiency.
[0033] In the present invention, by limiting the weight percentage of the liquid phase alloy Bi-Sn-Cu alloy and the solid phase Ni-Mo alloy in the solid-liquid dual-phase metal catalyst system, the effects of the two are fully exerted, so that when the solid-liquid dual-phase metal catalyst system is used to catalyze the cracking of alkanes, under the action of a low-blowing alkane gas flow, the Ni-Mo solid phase alloy continuously rolls and dynamically suspends in the Bi-Sn-Cu liquid phase alloy, thereby achieving a full contact reaction between the catalyst system and the alkane gas flow, and the Ni-Mo solid phase alloy rolls and is flushed by the alkane gas flow, so that the carbon powder generated by the cracking can quickly separate from the surface of the Ni-Mo solid phase catalyst, thereby effectively ensuring the catalytic activity of the solid phase catalyst and improving the alkane cracking rate and catalytic cracking efficiency.
[0034] When the solid-liquid biphase metal catalyst system provided by the present invention is used for alkane cracking, under the action of low-blowing alkane gas flow, the Ni-Mo solid phase alloy can continuously roll and dynamically suspend in the Bi-Sn-Cu liquid phase alloy, thereby achieving a full contact reaction between the catalyst system and the alkane gas flow, and under the flushing of the alkane gas flow, the carbon powder generated by the cracking can quickly detach from the surface of the Ni-Mo solid phase catalyst, thereby effectively ensuring the catalytic activity of the solid phase catalyst.
[0035] The present invention also provides a method for preparing the solid-liquid dual-phase metal catalyst system described in the above technical solution, comprising: heating Bi-Sn-Cu alloy and Ni-Mo alloy particles to 900-1000° C. to obtain a solid-liquid dual-phase metal catalyst system.
[0036] As an embodiment of the present invention, the mixing temperature of the Bi-Sn-Cu alloy and the Ni-Mo alloy particles can be 900-1000°C, or 950-960°C; the heating rate of the mixing temperature can be 200-250°C / h, or 210-230°C / h. In the present invention, by limiting the mixing temperature and the heating rate, it can be ensured that the liquid phase alloy and the solid phase alloy present a liquid phase and a solid phase respectively, giving full play to the catalytic ability of each of the two, and further improving the catalytic cracking reaction effect.
[0037] In the present invention, the method for preparing the Ni-Mo alloy particles preferably comprises the following steps:
[0038] (1) melting the alloy raw materials and refining them to obtain a Ni-Mo alloy melt;
[0039] (2) pouring and cooling the Ni-Mo alloy melt obtained in step (1) to obtain an alloy ingot; the cooling rate is 150 to 200° C. / min;
[0040] (3) Crushing the alloy ingot obtained in step (2) to obtain Ni-Mo alloy particles.
[0041] In the present invention, the alloy raw material is preferably melted and then refined to obtain a Ni-Mo alloy melt.
[0042] The present invention does not specifically limit the type of the alloy raw material, and an alloy raw material with a purity of ≥99.9% can be used. In an embodiment of the present invention, the alloy raw material is high-purity electrolytic nickel and high-purity molybdenum bars. In the present invention, by limiting the purity of the alloy raw material, the introduction of impurities that affect the catalytic activity of the alloy catalyst is avoided.
[0043] As an embodiment of the present invention, the melting temperature may be 1720-1780°C, or 1740-1760°C; the melting vacuum may be 0-3 Pa, or 1-2 Pa. In the present invention, by limiting the process parameters of melting the alloy raw material, it is ensured that the supersaturated Mo and the Ni matrix are fully fused.
[0044] As an embodiment of the present invention, the refining temperature may be 1720-1780°C, or 1740-1760°C; the refining time may be ≥2h, or ≥3h; the refining vacuum may be 0-3Pa, or 1-2Pa. In the present invention, by limiting the process parameters of the refining process, the refining effect is improved, and the catalytic activity of the solid phase alloy is further improved.
[0045] As an embodiment of the present invention, stirring can be performed during the refining; the stirring frequency can be 30 to 60 Hz, 35 to 50 Hz, or 40 to 45 Hz. In the present invention, by limiting the stirring rate, the mixing uniformity of Mo and Ni is improved, and the catalytic activity of the solid phase alloy catalyst is further improved.
[0046] As an embodiment of the present invention, the melting and refining devices may be ZrO2 prefabricated crucibles. In the present invention, by limiting the types of reaction devices, it is possible to avoid damaging the reaction devices during the reaction and introducing impurities into the alloy.
[0047] After obtaining the Ni-Mo alloy melt, the present invention preferably cools the Ni-Mo alloy melt after pouring to obtain an alloy ingot.
[0048] As an embodiment of the present invention, the pouring temperature may be 1830-1870° C., or 1850-1860° C. In the present invention, by limiting the pouring process parameters, the alloy composition is ensured to be uniform, the solidification and precipitation of Mo is avoided, and the catalytic activity of the alloy catalyst is further improved.
[0049] As an embodiment of the present invention, the cast iron ingot mold for casting can be a double-layer composite ingot mold; the inner cavity of the double-layer composite ingot mold is an arc-shaped graphite brick; the outer layer of the double-layer composite ingot mold is an austenitic heat-resistant steel ladle. In the present invention, by limiting the structure of the cast iron ingot mold for casting, the high density and high thermal conductivity of the arc-shaped graphite brick are utilized to enable it to withstand the scouring of the high-temperature Ni-Mo alloy solution without being damaged, thereby ensuring the alloy performance; at the same time, the austenitic heat-resistant steel ladle is used as the outer layer structure to prevent the device from cracking during the subsequent rapid cooling operation.
[0050] As an embodiment of the present invention, the cooling rate is 150-200°C / min, preferably 160-190°C / min, and more preferably 170-180°C / min. In the present invention, by limiting the cooling rate, the Ni-Mo alloy solution is quickly cooled, the precipitation of alloy components is avoided, and the catalytic performance of the alloy is further improved.
[0051] As an embodiment of the present invention, the cooling may be performed by cryogenic gas; the temperature of the cryogenic gas may be -196 to -190°C, or -195 to -192°C; the inlet pressure of the cryogenic gas may be ≥0.5MPa, or ≥0.8MPa; the flow rate of the cryogenic gas may be ≥30m 3 / min, also ≥35m 3 / min; the cooling time can be ≥10min, or ≥15min. In the present invention, by limiting the process parameters of the cooling process, it is ensured that the Ni-Mo alloy solution can be uniformly and fully cooled, so that the obtained steel ingot has uniform composition and is easy to break.
[0052] As an embodiment of the present invention, the cooling device can be an ingot mold chamber with 6 to 7 Φ50mm air inlet holes and exhaust holes arranged longitudinally on the two side walls. In the present invention, by limiting the position, number and aperture of the exhaust holes and air inlet holes in the cooling device, it is ensured that the low-temperature gas can pass through the ingot mold chamber smoothly and quickly, so as to achieve rapid cooling of the Ni-Mo alloy solution to below the solidification point.
[0053] After obtaining the alloy ingot, the present invention preferably crushes the alloy ingot to obtain Ni-Mo alloy particles.
[0054] The present invention has no particular limitation on the crushing method as long as the particle size of the Ni-Mo alloy particles is within a specified range.
[0055] The method for preparing the Ni-Mo alloy solid phase alloy provided by the present invention can achieve uniform mixing of Ni and Mo, make the two fully contact, and effectively improve the catalytic activity of the solid phase alloy.
[0056] In the present invention, the preparation method of the Bi-Sn-Cu alloy preferably comprises the following steps:
[0057] 1) melting the alloy raw materials and then smelting them to obtain a Bi-Sn-Cu alloy melt;
[0058] 2) The Bi-Sn-Cu alloy melt obtained in step 1) is poured and then cooled to obtain a Bi-Sn-Cu alloy.
[0059] In the present invention, the alloy raw materials are preferably melted and then smelted to obtain a Bi-Sn-Cu alloy melt.
[0060] The present invention has no special limitation on the alloy raw materials, and raw materials familiar to those skilled in the art can be used. In an embodiment of the present invention, the alloy raw materials are bismuth ingots, tin ingots and electrolytic copper plates.
[0061] As an embodiment of the present invention, the temperature of the chemical material can be 1280-1300°C, or 1285-1290°C; the pressure of the chemical material can be 0.11-0.15MPa, or 0.12-0.13MPa. In the present invention, by limiting the chemical material temperature, Bi, Sn and Cu are uniformly mixed, and the alloy performance is further improved.
[0062] As an embodiment of the present invention, the smelting temperature can be 1280-1300°C, or 1285-1290°C; the smelting pressure can be 0.11-0.15MPa, or 0.12-0.13MPa; the smelting time can be ≥1h, or ≥2h. In the present invention, by limiting the process parameters of the smelting process, the smelting effect is improved, and the catalytic performance of the alloy is further improved.
[0063] As an embodiment of the present invention, the smelting atmosphere may be an inert atmosphere. In an embodiment of the present invention, the smelting atmosphere may specifically be argon. In the present invention, by limiting the atmosphere of the smelting process, the contact between air and metal is avoided, the purity of the alloy is improved, and the catalytic activity of the alloy is further improved.
[0064] As an embodiment of the present invention, stirring can be performed after smelting; the stirring time can be 30 to 40 seconds, or 35 to 38 seconds; the stirring rate can be 30 to 60 Hz, or 40 to 50 Hz. In the present invention, the alloy solution after smelting is stirred to ensure that the metal raw materials in the system are evenly mixed.
[0065] After obtaining the Bi-Sn-Cu alloy melt, the present invention preferably cools the Bi-Sn-Cu alloy melt after pouring to obtain the Bi-Sn-Cu alloy.
[0066] As an embodiment of the present invention, the pouring temperature of the Bi-Sn-Cu alloy melt may be 1350-1400° C., or 1360-1380° C. In the present invention, by limiting the temperature of the pouring process, the segregation of alloy elements is avoided, and the catalytic performance of the alloy is further improved.
[0067] The present invention has no special limitation on the cooling of the Bi-Sn-Cu alloy melt after pouring, and cooling operations well known to those skilled in the art may be adopted.
[0068] As an embodiment of the present invention, the particle size of the Bi-Sn-Cu alloy may be 5 to 30 mm, or 10 to 20 mm; if the particle size of the Bi-Sn-Cu alloy is not within the above range, the Bi-Sn-Cu alloy may be crushed.
[0069] The preparation method of the Bi-Sn-Cu alloy liquid phase alloy provided by the present invention can realize uniform mixing of Bi, Sn and Cu, make the three fully contact, and effectively improve the catalytic activity of the solid phase alloy.
[0070] The solid-liquid dual-phase metal catalyst system prepared by the preparation method provided by the present invention can completely melt the liquid phase alloy, realize the suspension of the solid phase alloy in the liquid phase alloy, increase the reaction contact area of the catalyst system, and easily realize the separation of carbon powder products on the surface of the solid phase alloy, thereby ensuring the catalytic activity and effectively improving the alkane cracking rate and catalytic cracking efficiency.
[0071] The present invention also provides the use of the solid-liquid biphasic metal catalyst system described in the above technical solution or the solid-liquid biphasic metal catalyst system prepared by the preparation method described in the above technical solution in catalyzing alkane cracking reactions.
[0072] As an embodiment of the present invention, the reaction temperature of the alkane cracking can be 900-1000° C., or 930-960° C. In the present invention, by limiting the reaction temperature of the alkane cracking, it is possible to ensure that the solid-liquid biphase metal catalyst system maintains the liquid phase and the solid phase, thereby improving the catalytic activity of the catalyst system.
[0073] In order to further illustrate the present invention, the solid-liquid biphasic metal catalyst system provided by the present invention and its preparation method and application are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0074] Example 1
[0075] A solid-liquid dual-phase metal catalyst system, which is composed of 70% Bi-Sn-Cu alloy liquid and 30% Ni-Mo alloy particles by weight percentage;
[0076] In terms of weight percentage, the chemical composition of the Bi-Sn-Cu alloy is 35% Bi, 25% Sn and 40% Cu; the chemical composition of the Ni-Mo alloy is 58% Ni and 42% Mo;
[0077] The preparation method of the Bi-Sn-Cu alloy is:
[0078] (1) adding 58 kg of electrolytic nickel plates and 42 kg of high-purity molybdenum bars into a ZrO2 prefabricated crucible with a vacuum degree of 1 Pa, melting at 1750° C., and then refining at 1750° C. for 2 h to obtain a Ni-Mo alloy solution; wherein stirring is performed while refining, and the stirring frequency is 50 Hz;
[0079] (2) The Ni-Mo alloy solution obtained in step (1) was poured at 1850°C, and then cooled for 12 minutes using low-temperature nitrogen at a temperature of -196°C, with an inlet pressure of 0.55 MPa and a flow rate of 32 m / s. 3 / min; obtaining a steel ingot; the cooling rate is 180°C / min;
[0080] (3) crushing the steel ingot obtained in step (2) by using an impact drill and a jaw crusher, and screening to obtain Ni-Mo alloy particles with a particle size of 1 to 3 mm;
[0081] The preparation method of the Ni-Mo alloy comprises the following steps:
[0082] 1) In an argon atmosphere, 35 kg of bismuth ingots, 25 kg of tin ingots and 40 kg of electrolytic copper plates with their surfaces polished and scaled were added into a vacuum induction furnace at a pressure of 0.11 MPa, and the materials were melted at 1280°C, and then smelted at 1280°C for 1 h, and stirred at 30 s to obtain a Bi-Sn-Cu alloy solution;
[0083] 2) pouring the Bi-Sn-Cu alloy solution obtained in step 1) at 1350° C., crushing it with an impact drill and a jaw crusher after cooling, and screening to obtain a Bi-Sn-Cu alloy with a particle size of 5 to 30 mm;
[0084] The preparation method of the solid-liquid dual-phase metal catalyst system:
[0085] 35 kg of Bi-Sn-Cu alloy and 15 kg of Ni-Mo alloy particles were mixed and heated to 950° C. at a heating rate of 200° C. / h to obtain a solid-liquid dual-phase metal catalyst system.
[0086] Application Example 1
[0087] The solid-liquid biphasic metal catalyst system obtained in Example 1 was added to a cracking reactor, and methane gas was introduced from the bottom of the reactor at a rate of 20 L / h for catalytic cracking for 120 h to obtain 423 g of H2 and 1264 g of carbon powder; the reaction cracking rate was 98.4%, and the average cracking rate was 0.28 g / h / kg of catalyst.
[0088] Comparative Example 1
[0089] Comparative Example 1 is a Ni-Mo alloy solid catalyst, and the composition and preparation method of the Ni-Mo alloy solid catalyst are the same as those of Example 1.
[0090] Comparative Example 2
[0091] Comparative Example 2 is a Bi-Sn-Cu alloy liquid catalyst, and the composition and preparation method of the Bi-Sn-Cu alloy liquid catalyst are the same as those of Example 1.
[0092] Comparative application example 1
[0093] The difference between Comparative Application Example 1 and Application Example 1 is that the solid-liquid dual-phase metal catalyst system of Example 1 is replaced by the Ni-Mo alloy solid catalyst of Comparative Example 1;
[0094] The reaction produced 135.36 g of H2 and 391.87 g of carbon powder; the reaction cracking rate was 31.5%, and the average cracking rate was 0.09 g / h / kg of catalyst.
[0095] Comparative Application Example 2
[0096] The difference between comparative application example 2 and application example 1 is that the solid-liquid dual-phase metal catalyst system of example 1 is replaced by the Bi-Sn-Cu alloy liquid catalyst of comparative example 2;
[0097] The reaction yielded 287.4 g of H2 and 858.9 g of carbon powder; the reaction cracking rate was 66.9%, and the average cracking rate was 0.19 g / h / kg of catalyst.
[0098] By comparing Application Example 1 with Comparative Application Examples 1 to 2, it can be seen that the reaction cracking rate and average cracking rate of the solid-liquid biphasic metal catalytic system provided by the present invention are much higher than the reaction cracking rate and average cracking rate of using solid metal catalysts and liquid metal catalysts alone, indicating that the solid-liquid biphasic metal catalytic system provided by the present invention has excellent catalytic activity and can effectively catalyze the cracking reaction of alkane.
[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A solid-liquid dual-phase metal catalyst system, comprising a liquid phase alloy and a solid phase alloy; in terms of weight percentage, the content of the liquid phase alloy is 20-30%, and the content of the solid phase alloy is 70-80%; the liquid phase alloy is a Bi-Sn-Cu alloy, and the solid phase alloy is a Ni-Mo alloy.
2. The solid-liquid dual-phase metal catalyst system according to claim 1, characterized in that: Calculated by weight percentage, the chemical composition of the Bi-Sn-Cu alloy is 30-40% Bi, 20-30% Sn and 35-45% Cu.
3. The solid-liquid dual-phase metal catalyst system according to claim 1, characterized in that: Calculated by weight percentage, the chemical composition of the Ni-Mo alloy is 55-63% Ni and 37-45% Mo.
4. The solid-liquid biphase metal catalyst system according to claim 1 or 3, characterized in that: The particle size of the Ni-Mo alloy is 1 to 3 mm.
5. The solid-liquid dual-phase metal catalyst system according to claim 1, characterized in that: The density of the liquid phase alloy in the solid-liquid dual-phase metal catalyst system is 90-95% of the density of the solid phase alloy.
6. The method for preparing the solid-liquid biphasic metal catalyst system according to any one of claims 1 to 5, comprising: The Bi-Sn-Cu alloy and Ni-Mo alloy particles are heated to 900-1000° C. to obtain a solid-liquid dual-phase metal catalyst system.
7. The preparation method according to claim 6, characterized in that: The preparation of the Ni-Mo alloy particles comprises the following steps: (1) melting the alloy raw materials and refining them to obtain a Ni-Mo alloy melt; (2) pouring and cooling the Ni-Mo alloy melt obtained in step (1) to obtain an alloy ingot; the cooling rate is 150 to 200° C. / min; (3) Crushing the alloy ingot obtained in step (2) to obtain Ni-Mo alloy particles.
8. The method for preparing the adsorption material according to claim 6, characterized in that: The cooling in step (2) uses low-temperature gas; the temperature of the gas is -196 to -190°C, the inlet pressure is ≥0.5MPa, and the flow rate is ≥30m 3 / min; the cooling time is ≥10min.
9. Use of the solid-liquid biphasic metal catalyst system according to any one of claims 1 to 5 or the solid-liquid biphasic metal catalyst system prepared by the preparation method according to any one of claims 6 to 8 in catalyzing alkane cracking reactions.
10. The use according to claim 9, characterized in that: The reaction temperature of the alkane cracking is 900-1000°C.